Meningkatnya Jumlah Investor dalam Pasar Saham Indonesia Pada Era Pandemi Covid-19 - Masridha Masridha; Widya Dwi Syahprya; Yenni Samri Juliati Nasution (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The Covid 19 pandemic has also had a negative impact on the company, such as a decrease in share prices and financial performance, ehich can affect the company's value. Not a few of the company's employees were fired because of it. But why did so many people invest during the covid 19 pandemic? In fact, there has been an increase in the number of investors on the indonesian stock exchange market. In this study, we will idntify the factors that influence the increase in the number of investors on the indonesian stock exchange market. With qualitve research methods, descriptive, exploratory. The results of this study are that there are several factors that influence people to invest during the covid 19 pandemic, many people invest in pandemic conditions by conducting fundamental and technical analysis, conducting stock portfolios, choosing bussiness sectors that are still needed in pandemic conditions, and seeking the latest information issuer.